LAMP3 inhibits autophagy and contributes to cell death by lysosomal membrane permeabilization. Issue 7 (3rd July 2022) - Tanaka, Tsutomu; Warner, Blake M.; Michael, Drew G.; Nakamura, Hiroyuki; Odani, Toshio; Yin, Hongen; Atsumi, Tatsuya; Noguchi, Masayuki; Chiorini, John A.
ABSTRACT: Sjögren syndrome (SS) is a chronic and progressive autoimmune disease characterized by dry mouth and dry eyes, and characteristic autoantibodies. Evidence of altered macroautophagy/autophagy and apoptosis has been associated with SS, but a mechanistic understanding of the gene expression changes associated with these abnormal processes has not been realized. Recently, increased LAMP3 (lysosomal associated membrane protein 3) expression was found in a subset of SS patients and was associated with increased apoptosis and autoantigen accumulation and release. To better understand how LAMP3 expression might modulate apoptosis, cell biology, and biochemical studies were used to examine the effect of LAMP3 expression in minor salivary gland cells. LAMP3 expression resulted in degradation of LAMP1 increasing lysosomal membrane permeabilization and relocalization of cathepsins to the cytoplasm, resulting in destabilizing autophagic flux and caspase activation. These findings highlight the central role of LAMP3 expression in the pathogenesis of SS. Abbreviations: A253-control: A253 control for LAMP3 stable overexpression; A253- LAMP3: A253 LAPM3 stable overexpression; CASP1: caspase 1; CASP3: caspase 3; CHX: cycloheximide; CTSB: cathepsin B; CTSD: cathepsin D; CQ: chloroquine; DCs: dendritic cells; ER: endoplasmic reticulum; LGALS3: galectin 3; HCV: hepatitis C virus; HSG-control: HSG control for LAMP3 stable overexpression; HSG-LAMP3: HSG LAMP3 stable overexpression; HSP: heat shock protein; HTLV-1: human T-lymphocyte leukemia virus-1; IXA: ixazomib; LAMP: lysosomal associated membrane protein; MHC: major histocompatibility complex; mAb: monoclonal antibody; OE: overexpression; pepA: pepstatin A; pAb: polyclonal antibody; pSS: primary Sjögren syndrome; qRT-PCR: quantitative real- time reverse transcriptase polymerase chain reaction; SLE: systemic lupus erythematosus; SS: Sjögren syndrome; UPR: unfolded protein response; V-ATPase: vacuolar-type proton- translocating ATPase; Y-VAD: Ac-YVAD-cmk; Z-DEVD; Z-DEVD-fmk; Z-VAD: Z-VAD- fmk